Sensors and transducers - Sinclair, Ian Robertson (Oxford [England] ; Boston : Newnes, 2001)
In this book Ian Sinclair provides the practical knowhow required by technician engineers, systems designers and students. The focus is firmly on understanding the technologies and their different applications, not a mathematical approach. The result is a highly readable text which provides a unique introduction to the selection and application of sensors, transducers and switches, and a grounding in the practicalities of designing with these devices. The devices covered encompass heat, light and motion, environmental sensing, sensing in industrial control, and signal-carrying and non-signal switches. Get up to speed in this key topic through this leading practical guide Understand the range of technologies and applications before specifying Gain a working knowledge with a minimum of maths.
Preface; Strain and pressure; Position, direction, distance and motion; Light and associated radiation; Temperature sensors and thermal transducers; Sound, infrasound and ultrasound; Solids, liquids and gases; Environmental sensors; Other sensing techniques; Instrumentation techniques; Non-signal switches; Signal carrying switches; Index.
Includes index.
Keywords: Transducers; Detectors; Electronic books